'Is every YouTuber going to make a coming out video eventually?': YouTube celebrity video bloggers and lesbian and gay identity. Issue 1 (2nd January 2017) - Lovelock, Michael
ABSTRACT: A significant number of YouTube celebrity video bloggers (vloggers) have used the platform to come out publicly as lesbian or gay. This article interrogates the cultural work of YouTube celebrity coming outs, through the case studies of two of the most prominent gay vloggers: Ingrid Nilsen and Connor Franta. The article explores how the coming out moments of these vloggers, as articulated in their coming out vlogs and the wider media discourses surrounding these, make legible a normative gay youth subject position which is shaped by the specific tropes, conventions and commercial rationale of YouTube fame itself. I define this subject position as 'proto-homonormative'. It positions a 'successful' gay adulthood, defined through the neoliberal ideals of authenticity, self-branding and individual enterprise bound to the phenomenon of YouTube celebrity, as contingent upon a particular personal relationship with one's non-normative sexuality. I interrogate how the emotional contours of Nilsen and Franta's coming out narratives, their represented abilities to channel their non-normative sexualities into lucrative celebrity brands and their construction as gay and lesbian 'role models' by the mainstream media delineate a journey into 'acceptance' and 'pride' in one's gay sexuality as the expected narrative of contemporary gay life. This narrative, I argue, cements the default normativity of heterosexuality in mainstream culture, and produces a narrow framework of 'acceptable' gay youth subjectivity which is aligned with the ideals of neoliberalism embodied in the figure of the YouTube celebrity vlogger.